Facile one‐step synthesis of bio‐based AESO resins. Issue 10 (8th March 2016) - Wang, Chengshuang; Ding, Liang; He, Meng; Wei, Jun; Li, Juan; Lu, Rong; Xie, Hongfeng; Cheng, Rongshi
Abstract : In this study, the bio‐based thermosetting resins were synthesized via thiol‐ene coupling between acrylated epoxidized soybean oil (AESO) and different functionality of thiols. The structure of the AESO was carefully examined using FT–IR and 1 H‐NMR measurements. The thermal/mechanical properties of the bio‐based thermosetting resins were characterized using DMA, TGA, and tensile test. The DMA results showed that the storage moduli and glass transition temperatures of bio‐based thermosetting resins improved with increment of thiols functionality, meanwhile, the tensile strength, Young's modulus, and thermal stability of the AESO‐based resins also increased. Practical applications: The thermosetting resins were synthesized via thiol‐ene coupling between AESO and different functionality of thiols. This strategy has the potential for the fabrication of eco‐friendly bio‐based materials. The rapid and highly efficient strategy of thiol‐ene coupling was successfully applied for the preparation of eco‐friendly bio‐based thermosetting resins derived from AESO and different functionality of thiols. Abstract : The rapid and highly efficient strategy of thiol‐ene coupling was successfully applied for the preparation of eco‐friendly bio‐based thermosetting resins derived from AESO and different functionality of thiols.